2014
DOI: 10.1088/0029-5515/54/8/083003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the key role of the ion heat channel in the physics of the L–H transition

Abstract: Abstract.Experimental investigations carried out in the ASDEX Upgrade tokamak under various conditions demonstrate that the ion heat flux at the plasma edge plays a key role in the L-H transition physics, while the electron heat flux does not seem to play any role. This is due to the fact that the ion heat flux governs the radial electric field well induced by the main ions which is responsible for the turbulence stabilization causing the L-H transition. The experiments have been carried out in the low density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
223
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(258 citation statements)
references
References 36 publications
30
223
3
Order By: Relevance
“…Malkov and Diamond observed that the calculated power threshold attains a minimum at low density and maximum ion heating [60], but increases at low density and increased electron heating. Thus, the calculated power threshold exhibits a similar trend to the experimentally observed increase of the power threshold at low density with preferential electron heating [100,101].…”
Section: Heuristic Modelssupporting
confidence: 80%
See 2 more Smart Citations
“…Malkov and Diamond observed that the calculated power threshold attains a minimum at low density and maximum ion heating [60], but increases at low density and increased electron heating. Thus, the calculated power threshold exhibits a similar trend to the experimentally observed increase of the power threshold at low density with preferential electron heating [100,101].…”
Section: Heuristic Modelssupporting
confidence: 80%
“…L-mode outer-core turbulent transport and the relevant critical temperature/density gradients determine the ion pres sure gradient inside and across the separatrix. In AUG experiments, ion and electron thermal radial transport have been decoupled in low-density ECH plasmas, and the upturn in the L-H power threshold at low density has been attributed to the additional power loss in the electron channel at high-separatrix electron temperature [99][100][101]. After accounting for the additional electron-channel power loss, the L-H power threshold was found to increase in proportion to the ion heat flux.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results from JET with a Be/W and C wall show a correlation of the density roll-over to divertor geometry and divertor/wall materials [8]. On the other hand, experiments from ASDEX Upgrade demonstrate the key role played by the edge ion heat flux as an explanation for the strong increase in the L-H power threshold at low density with electron cyclotron resonant heating (ECRH) as the auxiliary heating power [33]. These findings show that the occurrence of the low density dependence of the power threshold is not a universal feature in various tokamaks.…”
Section: H-mode Accessmentioning
confidence: 99%
“…Previous work on the low density branch of the P LH threshold [15] had already indicated that the decoupling of ion and electron channel is responsible for the observed increase of P LH when applying ECRH at low density. Recent transport analyses in the low density branch, [16], reveal that the edge ion heat flux at the LH transition (Q i,edge ) increases linearly with density, despite the non-monotonic behavior of P LH , FIG. 2 left panel.…”
Section: L-h Transition and Pedestal Physicsmentioning
confidence: 99%